Evaluation of the ambulatory arterial stiffness index in patients with rheumatoid arthritis. Issue 5 (October 2015) - Karakulak, Ugur Nadir; Sahiner, Levent; Maharjan, Naresh; Okutucu, Sercan; Evranos, Banu; Aladag, Elifcan; Kilic, Levent; Akdogan, Ali; Kaya, Ergun Baris; Kabakci, Giray; Aytemir, Kudret
<x xml:space="preserve">Abstract</x> Objective Patients with rheumatoid arthritis (RA) are at a higher risk of arterial disease, endothelial dysfunction, and vascular inflammation than the general population. Therefore, these patients are prone to decreased arterial compliance and increased arterial stiffness. Ambulatory arterial stiffness index (AASI) was introduced as an index that predicts cardiovascular risk. In this study, the AASI was evaluated in RA patients. Method Thirty-three RA patients and 33 healthy age-matched and sex-matched individuals were evaluated according to the 24 h blood pressure (BP) profiles. The regression slope of diastolic over systolic BP was computed for each participant. AASI was defined as 1− regression slope. Results There was no significant difference in terms of the basic demographic characteristics, and average day, average night, and total average BP profiles as well as dipper status among the two groups. AASI was 0.45±0.12 and 0.38±0.10 in the RA patients and the healthy controls, respectively (P=0.019). AASI was not significantly different in women and men in both the groups. AASI was significantly higher in nondippers compared with dippers in the entire group and the RA group, but not in the control group. Independent predictors that were found to affect AASI in RA patients were age, nondipper status, VAS score, DAS28 score, and rheumatoid factor positivity. Conclusion AASI is higher in RA patients compared with healthy individuals. When the prognostic significance of AASI is considered, RA patients with higher AASI should be followed closely for future adverse cardiovascular outcomes.